RIFM fragrance ingredient safety assessment, p-tolyl acetate, CAS Registry Number 140-39-6. (December 2019) - Api, A.M.; Belmonte, F.; Belsito, D.; Biserta, S.; Botelho, D.; Bruze, M.; Burton, G.A.; Buschmann, J.; Cancellieri, M.A.; Dagli, M.L.; Date, M.; Dekant, W.; et al.
Abstract: Summary: The existing information supports the use of this material as described in this safety assessment. p- Tolyl acetate was evaluated for genotoxicity, repeated dose toxicity, reproductive toxicity, local respiratory toxicity, phototoxicity/photoallergenicity, skin sensitization, and environmental safety. Data from read-across analog ethyl p- tolyl carbonate (CAS # 22719-81-9) show that p- tolyl acetate is not expected to be genotoxic. Data on read-across materials p- cresol (CAS # 106-44-5) and acetic acid (CAS # 64-19-7) provide a calculated MOE >100 for the repeated dose and reproductive toxicity endpoints. The skin sensitization endpoint was completed using DST for reactive materials (64 μg/cm 2 ); exposure is below the DST. The phototoxicity/photoallergenicity endpoints were evaluated based on UV spectra; p- tolyl acetate is not expected to be phototoxic/photoallergenic. The local respiratory toxicity endpoint was evaluated using the TTC for a Cramer Class I material, and the exposure to p- tolyl acetate is below the TTC (1.4 mg/day).The environmental endpoints were evaluated; p- tolyl acetate was found not to be PBT as per the IFRA Environmental Standards, and its risk quotients, based on its current volume of use in Europe and North America (i.e., PEC/PNEC), are <1. Highlights: p -Tolyl acetate; a safety assessment based on RIFM's criteria. A safety assessment based on 7 human health endpoints plus environmental. All endpoints were cleared using target data, read-across, and/or TTC.